2015
DOI: 10.1089/scd.2014.0377
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Human Pluripotent-Stem-Cell-Derived Vascular Cells for Tissue Engineering Applications

Abstract: Tissue-engineered constructs are rendered useless without a functional vasculature owing to a lack of nutrients and oxygen. Cell-based approaches to reconstruct blood vessels can yield structures that mimic native vasculature and aid transplantation. Vascular derivatives of human induced pluripotent stem cells (hiPSCs) offer opportunities to generate patient-specific therapies and potentially provide unlimited amounts of vascular cells. To be used in engineered vascular constructs and confer therapeutic benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…There are several methods in the literature that describe the induction of differentiation of ES and iPS cells into ECs (29-37). Depending upon the main objectives of the downstream experiments, the methods for inducing ES and iPS cells could be different (29-37).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several methods in the literature that describe the induction of differentiation of ES and iPS cells into ECs (29-37). Depending upon the main objectives of the downstream experiments, the methods for inducing ES and iPS cells could be different (29-37).…”
Section: Methodsmentioning
confidence: 99%
“…Depending upon the main objectives of the downstream experiments, the methods for inducing ES and iPS cells could be different (29-37). To minimize contamination of unknown cells, we use monoclonal antibodies that recognize the extracellular domains of Flk-1 and VE-cadherin.…”
Section: Methodsmentioning
confidence: 99%
“…S3 A and B). EFNB2 and EPHB4 were the first identified and most widely used markers for AECs and VECs, respectively (6)(7)(8)(9)(10)(11)(12)(13)17). Specific targeting of the EFNB2 and EPHB4 locus was confirmed by junction PCR and Southern blot analysis (SI Appendix, Evaluation of Candidate Factors for Arteriovenous Specification.…”
Section: Significancementioning
confidence: 99%
“…Previous studies have shown progress in AEC differentiation (6)(7)(8)(9)(10)(11)(12)(13)(14), but the arterial-specific functions in vitro and the protection of ischemic tissue in vivo have not been well demonstrated in the resulting cells. Here, we use single-cell RNA sequencing (RNA-seq) of early mouse AECs and a CRISPR/Cas9-generated EFNB2-tdTomato/EPHB4-EGFP dual reporter human embryonic stem cell line to develop a protocol for differentiating human pluripotent stem cells into AECs using fully defined culture conditions.…”
mentioning
confidence: 99%
“…Differentiation into vascular cell types is enhanced by low oxygen conditions, which can be used to produce early vascular cells that can be further matured into pericytes and ECs [59,60]. A recent study found that increasing cell seeding density for spontaneous differentiation of EBs from PSCs resulted in cells with a mesenchymal-like morphology, which were supposedly perivascular precursors [61].…”
mentioning
confidence: 99%